Algorithm of passive “Beidou”/INS closed-loop integrated using two level filter - GAO Fa-qin; TAN Zhan-zhong (Tongxin xuebao)
One scheme of integrated navigation Kalman filter positioning algorithm was put forward to apply to “Beidou” and INS（intertial navigation system）.Using the pseudo-range’s velocity of changing as observations,on the basis of the high stable clock,a closed loop Kalman filtering model that can revise the attitude error of INS was put out,its biggest optimism was that it could change between the close-loop method and open-loop method steadily.Finally,by computer simulation,it explain that our scheme improve the positioning precision effectively when the satellites in sight are less then two ones,and it also show that our scheme can revise the attitude error of INS effectively and estimate the user’s velocity in high precision.